Impact of psychological capital (PsyCap) on affective commitment: mediating role of affective well-being. Issue 4 (20th January 2021) - Ribeiro, Neuza; Gupta, Manish; Gomes, Daniel; Alexandre, Nelia
Abstract : Purpose: The purpose of this study is to examine the mediating role of affective well-being (AWB) in the relationship between psychological capital (PsyCap) and affective commitment. Design/methodology/approach: The sample included 226 employees from diverse Portuguese organizations. Based on a survey, respondents reported their perceptions of own PsyCap, AWB and affective commitment to their organization. Findings: Results from structural equation modeling suggested presence of mediation by AWB in the relationship between PsyCap and affective commitment. Practical implications: Managers are encouraged to gain from this finding by emphasizing more on the emotional health of individuals to increase their attachment with the company. Originality/value: Though there are several studies indicating the positive consequences of PsyCap on employees, studies on how PsyCap affects affective commitment through AWB is scarce. These results advance the broaden-and-build theory by suggesting that the relationship between PsyCap and affective commitment is much more complex.